2017
DOI: 10.2298/jsc170306054g
|View full text |Cite
|
Sign up to set email alerts
|

Highly invasive alien plant Reynoutria japonica Houtt. represents a novel source for pharmaceutical industry - evidence from phenolic profile and biological activity

Abstract: Reynoutria japonica is on the IUCN list of the Worlds?100 worst invasive species, but it is also, especially its rhizome, an integral part of traditional chinese medicine. The objective of this study was to determine the amount of selected phenolic compounds in rhizome, stems, leaves and inflorescence methanol extracts of this plant, their antioxidant and anticholinesterase activity. The chemical profile of the examined extracts was obtained by a high-performance liquid chromatography. In vitro assays on DPPH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Many other beneficial properties have also been reported for RA including antinociceptive and neuroprotective effects. RA is found in a wide range of medicinal plant species including Rosmarinus officinalis L. (Lamiaceae), Apiaceae, Araliaceae, Cucurbitaceae, Rubiaceae, Plantaginaceae, and Polygonaceae (39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Many other beneficial properties have also been reported for RA including antinociceptive and neuroprotective effects. RA is found in a wide range of medicinal plant species including Rosmarinus officinalis L. (Lamiaceae), Apiaceae, Araliaceae, Cucurbitaceae, Rubiaceae, Plantaginaceae, and Polygonaceae (39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, we found that a Japanese knotweed extract exhibit high values of phenolic compounds [24][25][26]47], and hence, a DPPH analysis was performed to examine the antioxidant activity of our samples (Table 2). The analysis was performed on the liquid Japanese knotweed leaves extract, and the results showed very high antioxidant activity (81.36%).…”
Section: Samplementioning
confidence: 99%
“…It can also serve as a phytoremediator of heavy metals [ 19 ]. This plant presents many activities such as antioxidant [ 20 , 21 , 22 ], antiglycoxidative [ 23 ], anti-tyrosinase [ 24 , 25 , 26 , 27 ], antimycobacterial, antimicrobial, antidiabetic, anti-inflammatory, anticancer [ 18 , 28 , 29 , 30 ], gastroprotective [ 31 ], anti-cholinesterase [ 32 ] and gingival wound healing [ 33 ]. More recently, a study has demonstrated the effectiveness and safety of the plant for acute Respiratory Tract Infections (RTIs) in adults and children [ 34 ], and it can also fight the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different enzymatic mechanisms are then involved depending on the enzyme considered. Several types of knotweed extracts obtained with various extraction methods or isolated compounds can act as antioxidant agents [ 21 , 25 , 29 , 32 , 38 , 39 , 40 , 41 , 42 , 43 ] or skin whiteners [ 24 , 25 , 26 , 44 , 45 , 46 , 47 ] and can facilitate treatments for skin diseases [ 27 , 48 , 49 , 50 ]. Moreover, resveratrol is now an active ingredient broadly used in cosmetology and dermatology [ 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%